Challenges in Obtaining Informed Consent in Qualitative Research and Suggestions to Improve It- A Descriptive Qualitative Study - Sindhuri R; Amol Dongre (Medsci Publications, 2023)
Introduction: The dynamic and flexible nature of qualitative studies is expected to impose new challenges upon the researchers in obtaining informed consent. The study objectives were to explore the challenges perceived by the researchers in obtaining informed consent in qualitative research and their suggestions to improve it. Material and Methods: It was a descriptive qualitative study in which In-depth interviews were conducted among ten qualitative researchers purposively selected from one medical college in Puducherry. Transcripts prepared from the audio recordings were thematically analyzed manually. Results: The challenges identified were inadequate knowledge of the researcher in designing qualitative consent form, reluctance to sign consent document by participant, ensuring confidentiality and risk benefit communication. The main suggestions provided by the participants were to use of multimedia tools to improve their understanding and creating a rapport to enhance their trust to participate in the study. Conclusions: Since most of the challenges were related to the reluctance of participants to provide consent due to various reasons and lack of adequate knowledge of the researcher, creating a good rapport with the participants and providing simple information through multimedia approaches and ethical training of qualitative researchers will aid us to overcome majority of these challenges.